Isolation of b-Cyclodextrin Gycosyl Transferase (b-CGTase) Producing Bacteria from Potato Plantation Soil - Kurniadi, Helman; Sagita, Desi; Hartesi, Barmi (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
Cyclodextrin glycosyltransferase (CGTase) is an extracellular enzyme produced by several microorganisms, particularly bacteria, that converts starch into cyclodextrin (CD). CD has various applications in fields such as food, textiles, pharmaceuticals, chemistry, and biotechnology. The objective of this study was to isolate b-CGTase-producing bacteria from soil in a potato plantation located in Kerinci, and to conduct their characterization. Screening was conducted using Horikoshi agar media with phenolphthalein and methyl orange color indicators. The results indicated that one isolate, coded CK-2, produced the optimum b-CGTase enzyme when incubated for 30 hours at 37 ÂºC and pH 10. The CGTase enzyme converted starch to CD when incubated for 60 minutes at 37 ÂºC and pH 7. The CK-2 isolate was identified as monobacilli Gram-positive bacteria, having spores, positive in the catalase test, and motile. The study concluded that the bacteria producing b-CGTase enzyme are found in the soil of potato plantations in Kerinci, which is believed to originate from the genus Bacillus sp.